Influenza A Virus as a Predisposing Factor for Cryptococcosis - Oliveira, Lorena V. N.; Costa, Marliete C.; Magalhães, Thaís F. F.; Bastos, Rafael W.; Santos, Patrícia C.; Carneiro, Hellem C. S.; Ribeiro, Noelly Q.; Ferreira, Gabriella F.; Ribeiro, Lucas S.; Gonçalves, Ana P. F.; Fagundes, Caio T.; Pascoal-Xavier, Marcelo A.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Influenza A virus (IAV) infects millions of people annually and predisposes to secondary bacterial infections. Inhalation of fungi within the Cryptococcus complex causes pulmonary disease with secondary meningo-encephalitis. Underlying pulmonary disease is a strong risk factor for development of C. gattii cryptococcosis though the effect of concurrent infection with IAV has not been studied. We developed an in vivo model of Influenza A H1N1 and C. gattii coinfection. Coinfection resulted in a major increase in morbidity and mortality, with severe lung damage and a high brain fungal burden when mice were infected in the acute phase of influenza multiplication. Furthermore, IAV alters the host response to C. gattii, leading to recruitment of significantly more neutrophils and macrophages into the lungs. Moreover, IAV induced the production of type 1 interferons (IFN-α4/β) and the levels of IFN-γ were significantly reduced, which can be associated with impairment of the immune response to Cryptococcus during coinfection. Phagocytosis, killing of cryptococci and production of reactive oxygen species (ROS) by IAV-infected macrophages were reduced, independent of previous IFN-γ stimulation, leading to increased proliferation of the fungus within macrophages. In conclusion, IAV infection is a predisposing factor for severe disease and adverse outcomes in mice coinfected with C. gattii.